Truck parked in front of the Ziskind Research Laboratories located on Harvard Street or Monsignor Shea Road, ca. 1967 - Unknown (Tufts Archival Research Center, 2005)
5x7; note with photo places the location at Harvard St. or Monsignor Shea Rd.